Origin and emplacement of syn-orogenic Variscan granitoids in Iberia the Beiras massif - Azevedo, M. Rosário (2014)
The Beiras batholith consists of four main Variscan granitoid suites intruded into metasediments of Proterozoic-Cambrian and Palaeozoic age in Central Northern Portugal: a) the early, syn-D3 granodiorite-monzogranite suite (314-311 Ma); b) the highly peraluminous syn-D3 two-mica/leucogranite suite (308 Ma); c) the late-post-D3 granodiorite-monzogranite suite (306 Ma) and (d) the late-post-D3, peraluminous, biotite-muscovite granite suite (300-295 Ma). Major, trace and isotopic data suggest that the S-type synkinematic two-mica granites result from moderate degrees of partial melting under vapour absent conditions of middle crustal metasedimentary sources comparable to the Proterozoic-Cambrian metapelite-metagraywacke units presently exposed in the studied area. A major contribution from metaigneous lower crust materials and/or interaction with mantle derived magmas appears to be required to produce the early, syn-D3 granodiorite-monzogranite suite. The emplacement of large volumes of late-post-kinematic granites showing decoupled high-K calc-alkaline and peraluminous signatures documents the importance of combined fractional crystallization and mixing processes (AFC) in granite petrogenesis. In a scenario of post-collisional re-equilibration of a thickened lithosphere, asthenospheric mantle upwelling and underplating of abundant basaltic melts at base of the crust is thought to have lead to widespread dehydration melting of lower-to mid-crustal lithologies and consequent formation of peraluminous granite magmas (syn-D3 two-mica granites). Mixing to various degrees of anatectic crustal melts with a juvenile asthenospheric mantle component is considered the major controlling process involved in the production of the late-post-D3, high-K calc-alkaline suite. Concomitant fractional crystallization can explain the geochemical signatures of the more evolved rocks, including those of the late-post-D3, peraluminous, biotite-muscovite granites.